Community-Based Learning Models to Improve Educational Access in Rural Areas - Muhammad Jailani; Madhvi Bagla (Lembaga Penelitian dan Pendidikan (LPP) Kalibra, 2026)
Limited educational access remains a persistent challenge in rural areas due to geographical isolation, resource scarcity, and weak institutional support. Community-based learning models have emerged as a strategic response to these constraints by actively involving local actors, resources, and social capital in educational provision. This study aims to examine how community-based learning models improve educational access in rural contexts and to identify key mechanisms that support their effectiveness. The research adopts a systematic literature-based qualitative approach, drawing on peer-reviewed journal articles, dissertations, and international case studies published between 1978 and 2025. Data were analyzed through thematic synthesis to identify recurring patterns related to participation, governance, technology use, and learning outcomes. The findings indicate that community-based learning models enhance access by reducing structural barriers, increasing learner engagement, and aligning educational programs with local needs. Successful implementation depends on strong community participation, flexible learning structures, policy support, and appropriate use of digital technology. This study contributes to the literature by providing an integrated analytical framework that links community participation with educational access in rural areas. The results offer practical implications for policymakers, educators, and development agencies seeking sustainable solutions to rural education disparities.